Features of the socio-pedagogical profile of women of the first period of adulthood engaged in health fitness - Grygus, Igor; Rebrov, Volodymyr; Orel, Iryna (Journal of Education, Health and Sport, 2022)
Relevance. The modern reformation of society requires the correction of many aspects of a person’s life: increasing the level of health and motor activity, mobilizing of their psyche, increasing the level of physical fitness, which ensure their adaptation to new conditions and phenomena of life. Studying the socio-pedagogical profile of women in the first period of adulthood is an important research step. Research tasks. To determine the education, marital status, social status, history of physical activity, having of children, goals of classes, forms of classes, health status, smoking habits and regularity of morning gymnastics of women aged 23-27 years who are engaged in health fitness. Research results. Health fitness classes in the first period of adulthood allow not only improve or maintain the functional capabilities of women at a high level for a long time, but also create reliable conditions for the formation of stable motives and needs for motor activity in the following years of life. It was found that the majority of women (59.46%) have higher education, what indicates their high academic level and probably greater awareness of healthy lifestyles. More than half of the participants (51.35%) are married women, a significant proportion are also divorced (40.54%), what emphasizes their life experience in family relationships. The social status of the participants varies between working women (62.16%) and housewives (37.84%), what indicates the different level of involvement in the labor market and the impact on their lifestyle. Conclusions. There were some differences in educational level and marital status between women aged 23-25 and 26-27. Differences in physical activity goals, health assessment, and smoking habits were also found. In other aspects, such as social status, physical activity, having the children, form of classes and morning gymnastics, the differences between age groups were insignificant, according to which women of the first period of adulthood have similar socio-pedagogical influences.